Communication towards global connectivity - IEEE Malaysia International Conference on Communications (1993 : Kuala Lumpur); The Institute of Electrical and Electronics Engineers (Malaysia); IEEE Communication Society; Universiti Teknologi Malaysia (Kuala Lumpur : IEEE, 1993)
13